Obstetric Brachial Plexus Palsy: Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The functional outcome with conservative management of 186 patients with obstetrical brachial plexus palsy, evaluated between 1981 and 1993, is reviewed at the Children's National Medical Center, George Washington University, Washington, DC.